2018
DOI: 10.1080/2153599x.2018.1502678
|View full text |Cite
|
Sign up to set email alerts
|

Predicting age of atheism: credibility enhancing displays and religious importance, choice, and conflict in family of upbringing

Abstract: The cultural learning concept of Credibility Enhancing Displays (CREDs) concerns the extent to which behavioral models consistently live out their professed ideals. While researchers have suggested that past CRED exposure is an important variable for predicting who does and does not become a religious believer, it is unclear how CREDs relate to when a person rejects the religious beliefs modelled to them during their upbringing. Using a large sample of formerly believing atheists, two analyses assessed the abi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Here, recruitment was online without participant reimbursement (though several raffles were organised to stimulate participation), and participants were mostly recruited through online groups (Facebook pages or newsletters). This means that many of the secular individuals that were reached were involved in digital media and had an interest in, or were part of, a secular organisation (like much of the previous research, e.g., Kontala, 2016;Langston et al, 2020;Pasquale, 2009;Smith, 2017;Smith & Halligan, 2021). This may indicate that religious non-belief is an important component of their social identities, and it may be that secular individuals in the general population, outside these digital environments, are more indifferent to religion and less cross-culturally similar than the current sample, which warrants exploring.…”
Section: Discussionmentioning
confidence: 85%
“…Here, recruitment was online without participant reimbursement (though several raffles were organised to stimulate participation), and participants were mostly recruited through online groups (Facebook pages or newsletters). This means that many of the secular individuals that were reached were involved in digital media and had an interest in, or were part of, a secular organisation (like much of the previous research, e.g., Kontala, 2016;Langston et al, 2020;Pasquale, 2009;Smith, 2017;Smith & Halligan, 2021). This may indicate that religious non-belief is an important component of their social identities, and it may be that secular individuals in the general population, outside these digital environments, are more indifferent to religion and less cross-culturally similar than the current sample, which warrants exploring.…”
Section: Discussionmentioning
confidence: 85%
“…In other words, for example, factors such as the importance of religion in one's family and the family's religious background (e.g. Jewish; cf., [9]) exert similar influences on the religiosity of academics [26], as well as nonreligiosity in general [51]. In sum, variables like family income, marital status, number of children, age, race, political orientation, and geographic location, have all been found to impact the religiosity of academics and the general public [36], [58], [66], [89], (see also [46]).…”
Section: The Familiar Background Of Nonreligion and Conflict: Family And Evolutionmentioning
confidence: 99%
“…More recent surveys have supported this finding and showed that exposure to CREDs predicts deconversion better than other proposed mechanisms such as analytic thinking or existential insecurity (Gervais et al, 2021). Indeed, even among the formerly religious, greater childhood exposure to CREDs predicted remaining religious for longer (Langston et al, 2020). However, these studies are limited because they conflate the credibility of religious models with the religiosity of the household environment, so it is difficult to disentangle whether credibility uniquely increases religious commitment or whether people are simply more likely to remain religious as adults if they adopted religious belief from a young age and experienced more social pressure to remain religious as they grew older.…”
Section: Background Theory: Credibility Enhancing Displays and Religi...mentioning
confidence: 99%